The effects of neutron irradiation on oxidation behavior, microstructure and transformation temperatures of Cu-12.7 wt.% Al-5 wt.% Ni-2 wt.% - Mn shape memory alloy - Tatar, C; Zengin, R (Elsevier, 2005)
The effects of neutron irradiation on oxidation behavior, microstructure and transformation temperatures of CuAlNiMn shape memory alloy have been investigated. It is seen that irradiation leads to observable changes of structure, and decreased temperatures of the martensite <-> austenite phase transformation. Oxidation followed an Arrhenius relationship. An increase in activation energy of the oxidation reaction is observed due to applied irradiation. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: shape memory alloy; neutron irradiation; phase transformations; oxidation behavior